2017
DOI: 10.1099/jgv.0.000947
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of a species D human adenovirus provides evidence of a novel virus

Abstract: A human adenovirus (HAdV) species D, was isolated from a hospitalised child with severe lower respiratory infection. It was initially detected in the nasopharyngeal aspirate of the child followed by conventional PCR amplification of the hexon, penton base, and fibre genes. Sanger DNA sequencing and phylogenetic analyses showed characteristics of a recombinant genome not described before. Next Generation Sequencing analysis was performed to reconstruct its complete DNA genome after viral isolation in adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Human adenovirus is well-recognized as an important pathogen of respiratory tract infection in childhood [13]. More than 70 HAdV serotypes are further subdivided into seven species (A-G) [4, 5]; however, species B (HAdV-3,7,11 and 14), C (HAdV-1,2,5 and 6), and E (HAdV-4) are the ones most associated with respiratory infections [6]. Epidemiological studies have reported an approximately 5–10% HAdV-positive rate among acute respiratory tract infections in children [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Human adenovirus is well-recognized as an important pathogen of respiratory tract infection in childhood [13]. More than 70 HAdV serotypes are further subdivided into seven species (A-G) [4, 5]; however, species B (HAdV-3,7,11 and 14), C (HAdV-1,2,5 and 6), and E (HAdV-4) are the ones most associated with respiratory infections [6]. Epidemiological studies have reported an approximately 5–10% HAdV-positive rate among acute respiratory tract infections in children [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Very young children, elderly persons with underlying respiratory or cardiac disease, or immunocompromised persons are at high risk for severe HAdV infection, leading to multi‐system organ failure and death . More than 70 HAdV types divided into seven species (A to G) have been described; however, most common respiratory infections are associated with species B, C, and E . The most commonly detected HAdV types in the in the United States are C1, C2, B3, and C5 .…”
Section: Introductionmentioning
confidence: 99%
“…Adenovirus is a DNA virus responsible for varieties of human diseases that affect the gastrointestinal tract, respiratory tract, and eye [1]. There are seven species for adenovirus categorized from A to G with two subgroups [2,3]. The classification correlates with clinical presentation, antigenic like symptoms to severe infections with pneumonia and high mortality up to 50% in immunocompromised patients [9].…”
Section: Introductionmentioning
confidence: 99%